Deconstructing Equivalence in the Translation of Texts from French to Indonesian - Sajarwa Sajarwa (Humaniora, 2017)
Translation is a process of reproducing a source text (ST) in the equivalent target text (TT). The equivalence of translation includes the message of the text. Several factors such as writer, translator, publisher, reader, or spirit of certain era, determine the translation equivalency. In translation, equivalence is negotiated and transactioned; in consequence it is highly likely that the current equivalency will be different in the future. Deconstruction theory claims that the relationship between a signifier and a signified is inconstant; however, it can be “deferred” to obtain a new or different relationship. As a result, a meaning may change in accordance with the will of its user. The result of this research indicates four differences between TT1 and TT2 translation; (1) within a period of twenty years of social and political change (1990 – 2010), TT1 reveals regional issues, while TT2 reveals social class issues; (2) the TT2’s disclosure of meaning is more direct, open, and occasionally rude than the subtle and euphemistic TT1; (3) the TT2 tends to follow ideology of foreignization by inserting foreign words or words from the source language, while the TT1 tends to follow ideology of domestication; (4) there are different viewpoints between the TT1 translator and the TT2 translator.